Optimizing Lectures From a Cognitive Load Perspective. Issue 3 (6th October 2019) - Jordan, Jaime; Wagner, Jason; Manthey, David E.; Wolff, Meg; Santen, Sally; Cico, Stephen J.
Abstract: Lectures are a common instructional method in medical education. Understanding the cognitive processes and theories involved in learning is essential for lecturers to be effective. Cognitive load theory is one theory that is becoming increasingly recognized in medical education and addresses the appropriate use of one's working memory. Memory is essential to knowledge acquisition. Two types of memory can be considered, working memory (processing of information) and long‐term memory (storage of information). Working memory has a limited capacity. Cognitive load refers to the amount of information processing activity imposed on working memory and can be divided into three domains: intrinsic, extraneous, and germane. By attending to cognitive load, educators can promote learning. This paper highlights various ways of improving cognitive load for learners during lecture‐based instruction by minimizing extraneous load, optimizing intrinsic load, and promoting germane load.